ANALISIS SISTEM AKUNTANSI KEUANGAN DAERAH, PEMANFAATAN TEKNOLOGI, DAN SISTEM PENGENDALIAN INTERNAL TERHADAP KUALITAS LAPORAN KEUANGAN DENGAN KOMPETENSI SUMBER DAYA MANUSIA SEBAGAI VARIABEL MODERASI: (STUDI KASUS PADA SKPD KOTA SURAKARATA) - Ika Arum Nurisma; Maya Widyana Dewi; Yuwita Ariessa Pravasanti (CV. Denasya Smart Publisher, 2024)
This study aims to examine the influence of the implementation of local government financial accounting systems, utilization of technology, and internal control systems on the quality of financial reports with human resource competence as a moderating variable. The data used in this research are primary data collected through a questionnaire distributed directly to respondents. The questionnaire was distributed to 100 employees in the finance and administrative departments of 25 SKPD in the city of Surakarta. The data analysis method used is Moderated Regression Analysis (MRA). The results of this study indicate that the implementation of local government financial accounting systems, utilization of technology, and internal control systems have an impact on the quality of financial reports. Furthermore, this research also proves that human resource competence is able to moderate the influence of local government financial accounting systems on the quality of financial reports. However, in this study, human resource competence was not able to moderate the influence of technology utilization and internal control systems on the quality of financial reports.